CRIMINAL LAW POLICY IN THE JUVENILE CRIMINAL JUSTICE SYSTEM FOR RECIDIVIST OFFENDERS IN INDONESIA - Aisyah, Wan Mutiara; Abdurrakhman Alhakim; Emiliya Febriyani (Universitas Bengkulu, 2024)
Indonesia is a nation that regards human rights as a core principle. Ensuring the protection of human rights is a crucial responsibility of the Indonesian government, including extending this protection to juvenile offenders. Despite having a structured legal framework within the juvenile justice system, issues persist, particularly concerning juvenile recidivism in Batam City. Although Batam has been recognized as a Child-Friendly City, the problem of juvenile recidivism remains unresolved. This study aims to evaluate the fulfillment of criminal law policies for juvenile recidivists and the challenges they face within the legal system. The method employed is empirical legal research analyzing juvenile recidivism data from the Batam District Court for 2021–2023. The legal theories used to analyze this study include Lawrence M. Friedman’s Legal System Theory and the Dignified Justice Theory. The findings indicate that current criminal law policies regarding juvenile recidivism in Batam City are not fully effective, with challenges arising from legal loopholes and limitations in diversion programs for repeat offenders. Keywords: Juvenile criminal justice, Recidivism, Legal Policy